How We Treat Drug-Susceptible Pulmonary Tuberculosis: A Practical Guide for Clinicians - Riccardi, Niccolò; Occhineri, Sara; Vanino, Elisa; Antonello, Roberta Maria; Pontarelli, Agostina; Saluzzo, Francesca; Masini, Tiziana; Besozzi, Giorgio; Tadolini, Marina; Codecasa, Luigi (Antibiotics (Basel), 2023)
Tuberculosis (TB) remains one of the leading causes of morbidity and mortality worldwide and pulmonary TB (PTB) is the main variant responsible for fueling transmission of the infection. Effective treatment of drug-susceptible (DS) TB is crucial to avoid the emergence of Mycobacterium tuberculosis-resistant strains. In this narrative review, through a fictional suggestive case of DS PTB, we guide the reader in a step-by-step commentary to provide an updated review of current evidence in the management of TB, from diagnosis to post-treatment follow-up. World Health Organization and Centre for Diseases Control (CDC) guidelines for TB, as well as the updated literature, were used to support this manuscript.